Light-sheet 3D microprinting via two-colour two-step absorption - Hahn, Vincent; Rietz, Pascal; Hermann, Frank; Müller, Patrick; Barner-Kowollik, Christopher; Schlöder, Tobias; Wenzel, Wolfgang; Blasco, Eva; Wegener, Martin (Nature photonics, 2022)
High-speed high-resolution 3D printing of polymers is highly desirable for many applications, yet still technologically challenging. Today, optics-based printing is in the lead. Projection-based linear optical approaches have achieved high printing rates of around 106 voxels s-1, although at voxel volumes of >100 μm3. Scanning-based nonlinear optical approaches have achieved voxel volumes of <1 μm3, but suffer from low printing speed or high cost because of the required femtosecond lasers. Here we present an approach that we refer to as light-sheet 3D laser microprinting. It combines image projection with an AND-type optical nonlinearity based on two-colour two-step absorption. The underlying photoresin is composed of 2,3-butanedione as the photoinitiator, (2,2,6,6-tetramethylpiperidin-1-yl)oxyl as the scavenger and dipentaerythritol hexaacrylate as the multifunctional monomer. Using continuous-wave laser diodes at 440 nm wavelength for projection and a continuous-wave laser at 660 nm for the light-sheet, we achieve a peak printing rate of 7 × 106 voxels s-1 at a voxel volume of 0.55 μm3.
Gesehen am 26.10.2022